Cardiopulmonary Fitness and Heart Rate Recovery as Predictors of Mortality in a Referral Population. Issue 2 (24th March 2014) - Dhoble, Abhijeet; Lahr, Brian D.; Allison, Thomas G.; Kopecky, Stephen L.
Abstract : Background: Exercise testing provides valuable information in addition to ST‐segment changes. The present study evaluated the associations among exercise test parameters and all‐cause mortality in a referral population. Methods and Results: We examined conventional cardiovascular risk factors and exercise test parameters in 6546 individuals (mean age 49 years, 58% men) with no known cardiovascular disease who were referred to our clinic for exercise stress testing between 1993 and 2003. The association of exercise parameters with mortality was assessed during a follow‐up of 8.1±3.7 years. A total of 285 patients died during the follow‐up period. Adjusting for age and sex, the variables associated with mortality were: smoking, diabetes, functional aerobic capacity (FAC), heart rate recovery (HRR), chronotropic incompetence, and angina during the exercise. Adjusting for cardiovascular risk factors (diabetes, smoking, body mass index, blood pressure, serum total, HDL, LDL cholesterol, and triglycerides) and other exercise variables in a multivariable model, the only exercise parameters independently associated with mortality were lower FAC (adjusted hazard ratio [HR] per 10% decrease in FAC, 1.21; 95% confidence interval [CI], 1.13 to 1.29; P <0.001), and abnormal HRR, defined as failure to decrease heart rate by 12 beats at 1 minute recovery (adjusted HR per 1‐beat decrease, 1.05; 95% CI, 1.03 to 1.07; P <0.001). The additive effects of FAC and HRR on mortality were also highly significant when considered as categorical variables. Conclusion: In this cohort of patients with no known cardiovascular disease who were referred for exercise electrocardiography, FAC and HRR were independently associated with all‐cause mortality.